Implementation of Long-Project Storytelling in Developing Children’s Creativity Through the Reggio Emilia Approach - Rachmawati, Yeni; Asyari, Sherin Maudri; Djoehaeni, Heny; Setiasih, Ocih; Listiana, Aan (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
The development of creativity is an educational demand in the 21st century. This writing aims to discuss briefly the implementation of long-project storytelling in early childhood education and its implications for developing children’s creativity. The method used is Early Child Research and Practice (ECRP) with data collection techniques through observation, documentation and field notes on teachers and children. The research was conducted at the Bunda Balita Playgroup, Bandung City. The long-project storytelling was conducted in three meetings. The researchers explored the theme of learning about houses and the sub-theme of learning about various forms of houses (fairy houses). The learning innovation conducted in the long-project storytelling method is by implementing the Reggio Emilia learning approach.  It shows learning activity by utilizing existing resources in the school environment. Through the long-project storytelling learning method, children experience an increased profile of language development. This can be seen when they can listen attentively to stories and answer the teacher’s questions enthusiastically. Researchers came up with creative ideas that emerged within children, including aspects of fluency, flexibility, originality, aspects of detail or elaboration, and aspects of working together in creativity (teamwork and creativity).